Implementación de la contabilidad comercial por el sistema de cuenta permanente en la ferretería D y J de la ciudad de Loja, periodo enero – marzo del 2015 - Jaramillo Troya, Elita Margoth (2017)
The development of this thesis was made for two reasons: first because it is a prerequisite for obtaining a degree in Accounting and Auditing Accountant, CPA Auditor, treatment was subject to Academic Regulations were in force at the National University Loja and secondly to implement and strengthen the knowledge acquired during the university education in Distance Learning mode. Your application is considered important because now every business, company or organization, is focused on economic growth and for that reason you need to have a proper accounting system in its activities, it will prevent the loss, misuse and theft up of material and financial resources. "Implementation of the Hardware Business Accounting Convention for the city of Loja, May-July period of 2015," allowed meet the objectives among which are the following: Preparation of Initial Inventory through a physical realization of their assets and liabilities, and design a plan that allowed Accounts Manual organize and record daily information from the hardware store, and finally applied the accounting process for preparing the financial statements that reflect the company's current situation. Upon completion of the accounting process and the results, it was found that the Hardware Palacios presents a considerable loss, reflecting the inadequate management of administration and financial resources, therefore it is recommended to continue maintaining its owner with commercial accounting the purpose of economic and financial information to help you make the necessary corrections and timely to stay in the local market.